Islamic Art And Eschatology In The Kemas Community Dakwah At Media: An Quran Rhetorical Approach - Mohd Nathir, Khairul Asyraf; Samah, Rosni; Nawi, Amani; Abdul Majid, Mohamad Yazid; Abd Zaman, Bushro (Ijaz Arabi Journal of Arabic Learning, 2025)
This study examines the concept of eschatology in Arabic literature, focusing on the "al-Wa'dzu" (warning) element in the Quran. Its primary goal is to analyse the rhetorical aspects of Islamic art within the KEMAS community. Previous research highlights the extensive use of rhetoric in interpreting Quranic eschatological verses. However, this approach remains underutilized in Islamic art, where the "al-Wa'dzu" aspect is not prominently emphasized for the target audience. Data will be collected through observation at the Islamic Festival organized by KEMAS Malaysia, following a qualitative methodology centered on observational data. The "Dakwah @ Media" program presents Islamic art characteristics to the audience, with key topics covering parenting, the life of Prophet Muhammad, and Islamic values. However, most presenters do not connect these topics to eschatological concepts, even when the content relates directly to the signs of eschatology in Islam.